Анна Каренина: роман в 8 частях (Л. Н. Толстой) - Толстой Лев Николаевич (Классика, 1997)
Экземпляры: ф.21 (2000) / Инвентарный номер: 41959 / Цена: / Сис.шифр: 84(2Рос=Рус)1-4 / Авт.знак: Т 53 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)1-44